Gloss and Speed Judgments Yield Different Fine Tuning of Saccadic Sampling in Dynamic Scenes. (December 2019) - Toscani, Matteo; Yücel, Ezgi I.; Doerschner, Katja
Image motion contains potential cues about the material properties of objects. In earlier work, we proposed motion cues that could predict whether a moving object would be perceived as shiny or matte. However, whether the visual system uses these cues is still uncertain. Herein, we use the tracking of eye movements as a tool to understand what visual information observers use when engaged in material perception. Observers judged either the gloss or the speed of moving blobby shapes in an eye tracking experiment. Results indicate that during glossiness judgments, participants tend to look at gloss-diagnostic dynamic features more than during speed judgments. This suggests a fine tuning of the visual system to properties of moving stimuli: Task relevant information is actively singled out and processed in a dynamically changing environment.